2014
DOI: 10.3329/jme.v44i1.19498
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Ni ALLOY ELECTRODEPOSITION FROM SIMPLE AND COMPLEX TYPE SULFATE ELECTROLYTES CONTAINING Ni/Fe RATIO OF 1 AND 12

Abstract: Iron-nickel (Fe-Ni) alloy electrodeposition has been conducted from simple and complex baths having Ni/Fe ratio of 1 and 12. The applied current density varies from 30 to 100 mA/cm2. The coating composition, morphology and microhardness are measured and characterized by SEM/EDX and Shimadzu microhardness tester. The percentage of Ni in the coating increases with increasing current density and the Ni/Fe ratio of electrolytes which is supported by the alloy deposition principle. Fine grained and smooth coating w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Therefore, Fe in the Ni-matrix causes replacement of a component of Ni-matrix composite coating by a cost-effective material. Literature survey also reveals that a variety of particulates such as SiC, TiO 2 , Al 2 O 3 and TiC have been added to the electroplating baths to form metal composite coatings [45,46]. Also, the strength and corrosion resistance can be significantly enhanced by introducing second phase ceramic particles into the Ni-Fe matrix [46,47].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Fe in the Ni-matrix causes replacement of a component of Ni-matrix composite coating by a cost-effective material. Literature survey also reveals that a variety of particulates such as SiC, TiO 2 , Al 2 O 3 and TiC have been added to the electroplating baths to form metal composite coatings [45,46]. Also, the strength and corrosion resistance can be significantly enhanced by introducing second phase ceramic particles into the Ni-Fe matrix [46,47].…”
Section: Resultsmentioning
confidence: 99%
“…Summing up the results of the analysis of chemical characteristics of hydrolysis of ferric chloride, it should be noted that researchers in over 65 years [2] conducted NiFe alloy plating and receive preferential deposition of iron in relation to nickel in all formulations electrolyte. Electrolytes used [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] is characterized by a wide range of molar relationship of nickel and iron. The cause of the anomalous codeposition of preferential deposition of iron sources previously not associated with the main feature of iron ionsthe existence of variable Valence iron one and two values in the charge of ions during the hydrolysis of iron salts.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous variation of the duty cycle between 90% and 20% resulted in a multilayer structure with alternating 28 Wt% Fe and 55 Wt% Fe, and the elemental variation brought about a significant increase in the microhardness, shear strength and wear resistance of the coatings. M. Moniruzzaman 15 et al found that the Ni content in the coating increased with the increase of current density and Ni content in the bath, which made the grain size decrease and the microhardness increase. Although changing the ECD parameters can cause changes in elemental content and properties, the electrodeposited layer usually suffers from defects such as pinholes, pits and cracks due to the influence of hydrogen evolution, 16 which limits the further improvement of Fe-Ni coatings.…”
mentioning
confidence: 99%